Carbon quantum dots synthesized from Plectranthus Amboinicus: An eco-friendly material with excellent non-linear optical properties. (2021) - Sunitha, A.P.; Sandeep, K.; Rose, Josny; Hajara, P.; Saji, K.J.
Highlights: Eco-friendly carbon dots. Preparation from natural extracts. Non-linear optical behavior Reverse saturable absorption is rarely reported. Abstract: Eco- friendly carbon dots synthesized from green resources are proposed as active material for light energy harvesting, opto-electronic devices, bio- labeling and display applications. Herein, we synthesized carbon dots from the leaf extracts of a medicinal plant Plectranthus amboinicus. These carbon dots were characterized by microscopic, spectroscopic and scattering techniques. Interestingly, when we used, 532 nm, pulsed Nd-YAG laser with a repetition rate of 10 Hz, we observed a reverse saturable absorption for these carbon dots on z scan. On analyzing the reverse saturable absorption pattern, it was found that it fits perfectly for two photon absorption. A material with two photon absorption can be used for the next generation light energy harvesting devices and bio-labelling/bio-imaging applications.